KONSEP KENEGARAAN DALAM PEMIKIRAN POLITIK AL-MAWARDI - Sholehuddin, Moh. (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2014)
This article is a literature study on the concept of state of al-Ma Wardi. In this context, his thoughts on the relationship between the ahl al-'aqd wa al-hall with the caliph and people are interesting matter to be explored. The focus of the articleis how the relationship between the leader and his people should be. The result of this study indicates that the relation between a caliph and the people is a social contract, i.e. common agreement to performduties and obligations based on mutual relation. Therefore, the people should obey their caliph and at the same time a caliph has the duty to protect his people and responsible for them as their leader. Social contract theory of al-Ma> Wardi, which has been written in the 11th century AD, has inspired political theory of a number of Western thinkers such as Hubbert Languet (1519-1581 AD), Thomas Hobbes (1588-1679 AD), and John Locke (1632-1604 AD).